Early reconstruction of bone defect created after initial surgery of a large keratocystic odontogenic tumor: A case report - Matijević, Stevo B; Damnjanović, Zoran R; Cerović, Snezana J (Vojnosanitetski pregled, 2017)
Introduction. Keratocystic odontogenic tumor (KCOT) is defined as a benign cystic neoplasm of the jaws of odontogenic origin with a high rate of recurrence. The most lesions occur in the posterior part of the mandible. Treatment of KCOT remains controversial, but the goals of treatment should involve eliminating the potential for recurrence while minimizing surgical morbidity. However, another significant therapeutic problem related to the management of KCOT is an adequate and early reconstruction of the existing jaw defect, as well as appropriate aesthetic and functional rehabilitation of a patient, especially in cases of a very large destruction of the jaws bone. Case report. We presented a 65-year-old female patient with very large KCOT of the mandible. Orthopantomographic radiography showed a very large elliptical multilocular radiolucency, located on the right side of the mandible body and the ascending ramus of the mandible, with radiographic evidence of cortical perforation at the anterior border of the mandibular ramus and the superior border of the alveolar part of the mandible. The surgical treatment included two phases. In the first phase, the tumor was removed by enucleation and additional use of Carnoy solution, performing peripheral ostectomy and excision of the affected overlying mucosa, while in the second phase, restorative surgery of the existing mandibular defect was performed 6 months later. Postoperatively, we did not register any of postoperative complications, nor recurrence within 2 years of the follow-up. Conclusion. Adequate and early reconstruction of the existing jaw defect and appropriate aesthetic and functional rehabilitation of the patient should be the primary goal in the treatment of KCOT, having in mind the need for a long-term post-surgical follow-up.